2002
DOI: 10.1128/aem.68.2.963-967.2002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Growth Inside Insulated External Walls as an Indoor Air Biocontamination Source

Abstract: The association between moisture-related microbial growth (mesophilic fungi and bacteria) within insulated exterior walls and microbial concentrations in the indoor air was studied. The studied apartment buildings with precast concrete external walls were situated in a subarctic zone. Actinomycetes in the insulation layer were found to have increased concentrations in the indoor air. The moisture content of the indoor air significantly affected all measurable airborne concentrations.Concrete sandwich facade pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Other studies have indicated that wooden materials offer more favorable conditions for fungal growth than other building materials (Meklin et al., 2003; Pietarinen et al., 2008). Water condensation can be particularly problematic inside the structure of walls (Burge, 2002; Pessi et al., 2002), and moisture and mold problems in Swedish buildings may be more frequently located inside the building construction in floors and walls (Bornehag et al., 2001; Roussel et al., 2008). One limitation of our data is that we have no information about the type of wall construction, only the external material.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that wooden materials offer more favorable conditions for fungal growth than other building materials (Meklin et al., 2003; Pietarinen et al., 2008). Water condensation can be particularly problematic inside the structure of walls (Burge, 2002; Pessi et al., 2002), and moisture and mold problems in Swedish buildings may be more frequently located inside the building construction in floors and walls (Bornehag et al., 2001; Roussel et al., 2008). One limitation of our data is that we have no information about the type of wall construction, only the external material.…”
Section: Discussionmentioning
confidence: 99%
“…Moisture is one of the most potent contributors to microbial survival in air and on surfaces [100][101][102][103], including resistance to electrostatic charges on surfaces [104], microbial activity [86,105], and the structure of the microbial community overall as survivors prosper [34,56,106]. The ability of microbial cells or spores to become aerosolized from surfaces and be resuspended into air due to occupant traffic or disturbance [107,108] is increased by a lowrelative humidity [109].…”
Section: Moisture and Relative Humiditymentioning
confidence: 99%
“…Other studies have reported higher airborne fungal concentrations in moisture and mould problem buildings than in non-mouldy buildings (Gorny et al, 1999;Hyvärinen et al, 1993;Haas et al, 2007;Macher et al, 1991;Miller et al, 2000;Pessi et al, 2002;Salonen et al 2007). …”
Section: Total Concentration Of Culturable Bacteria and Fungimentioning
confidence: 99%